Foreign policy and development models. Argentina and Brazil in comparative perspective (1930-2010) - Pereyra Doval, María Gisela (Universidad del Pacífico, 2017)
The main objective of this paper is to analyze how the Argentine and Brazilian governments that have adopted a series of different development models used foreign policy to achieve their goals from 1930 to 2010. We link development and foreign policy studies, understood as a key pairing for the understanding of the results obtained in these countries. This approach is also used to compare the performance of Argentina and Brazil from this perspective.